Perancangan Business Intelligence sebagai Sistem Pendukung Peningkatan Kinerja Perusahaan di CV. 2nd Machine - Warsa Setiawan Surmadi; Rakhmat Ceha; Djamaludin (Bandung Conference Series: Industrial Engineering Science, 2022)
Abstract. CV. 2nd Machine is a company that focuses on selling all kinds of overseas factory machines such as Panasonic, Sanyo, Denki, Toshiba, and Samsung. Machines that have been ordered from abroad are not allowed in intact condition. Therefore, the machine must first be disassembled into small parts. This is done because the rules for selling machines abroad may not be intact or functioning. Then the goods that have arrived in Indonesia in separate components are transferred to the company's warehouse in Cimahi. CV 2nd Machine has two warehouses for the storage of its goods. The goods that have been allocated to the warehouse are then sorted again to see if there are components that can be put together for reconditioning or spare parts taken for sale at the main store in Kopo. Sales of the company's products are carried out online and offline. Business intelligence (BI) is a collection and series of activities or stages to obtain data and analyze data so that it can be used in a decision-making process that is useful and on target for a problem. In implementing the BI system, a data warehouse (DW) is needed which is a collection of various raw data sources that are integrated with each other so that they meet the needs, usually in the form of query analysis processing. The basic function of a data warehouse is to provide a variety of data from the perspective of business analysis and decision makers. In a data warehouse, a database is needed to describe the data, the definition of each table, the data storage structure, and the ETL process. The results obtained from the application of business intelligence systems in sales include systems that can be accessed by the finance and marketing department. Broadly speaking, the relationship formed from the three parts is that the marketing department creates transaction documents which are then submitted to the finance department. The transaction data will then be managed by the finance department to report the company's financial condition. The results of the reporting are in the form of a dashboard that displays company sales data carried out during the 2020 pandemic. Abstrak. CV. 2nd Machine adalah perusahaan yang fokus menjual segala macam mesin pabrik di luar negeri seperti Panasonic, Sanyo, Denki, Toshiba, dan Samsung. Mesin yang dipesan dari luar negeri tidak diperbolehkan dalam keadaan utuh. Oleh karena itu, mesin harus dibongkar terlebih dahulu menjadi bagian-bagian kecil. Hal ini dilakukan karena aturan penjualan mesin ke luar negeri mungkin tidak utuh atau tidak berfungsi. Kemudian barang yang sudah sampai di Indonesia dalam komponen terpisah dipindahkan ke gudang perusahaan di Cimahi. CV 2nd Machine memiliki dua gudang untuk penyimpanan barangnya. Barang-barang yang telah dialokasikan ke gudang kemudian disortir kembali untuk melihat apakah ada komponen yang dapat disatukan untuk rekondisi atau suku cadang diambil untuk dijual di toko utama di Kopo. Penjualan produk perusahaan dilakukan secara online dan offline. Business Intelligence (BI) adalah kumpulan dan rangkaian kegiatan atau tahapan untuk memperoleh data dan menganalisis data sehingga dapat digunakan dalam proses pengambilan keputusan yang bermanfaat dan tepat sasaran untuk suatu masalah. Dalam mengimplementasikan sistem BI diperlukan data warehouse (DW) yang merupakan kumpulan dari berbagai sumber data mentah yang saling terintegrasi sehingga memenuhi kebutuhan, biasanya berupa pengolahan analisis query. Fungsi dasar dari data warehouse adalah untuk menyediakan berbagai data dari perspektif analisis bisnis dan pengambil keputusan. Dalam data warehouse, database diperlukan untuk mendeskripsikan data, definisi setiap tabel, struktur penyimpanan data, dan proses ETL. Hasil yang diperoleh dari penerapan sistem business intelligence dalam penjualan meliputi sistem yang dapat diakses oleh bagian keuangan dan pemasaran. Secara garis besar hubungan yang terbentuk dari ketiga bagian tersebut adalah bagian pemasaran membuat dokumen transaksi yang kemudian diserahkan ke bagian keuangan. Data transaksi tersebut selanjutnya akan dikelola oleh bagian keuangan untuk melaporkan kondisi keuangan perusahaan. Hasil pelaporan berupa dashboard yang menampilkan data penjualan perusahaan yang dilakukan selama masa pandemi 2020.